Manajemen Stres pada Mahasiswa dalam Penyusunan Skripsi di Institut Pertanian Bogor - Nabila Nabila; Andita Sayekti (IPB University, 2021)
Final project is an independent task that must be completed by final year undergraduate students as a graduation requirement. The process includes the preparation stage (proposal), implementation, thesis writing, and thesis defense. The purpose of this study is determine the symptoms of stress experienced by final year students, knowing the stress factors, and determine alternative stress management in writing their thesis. The method that used is non-probability sampling with a quota sampling technique. Total sample is 419 respondents. Descriptive and factor analysis are used for analytical tools. The results stated that IPB students felt stressed during the preparation of the thesis with physical symptoms that were felt easily tired and heart palpitations. The most contributing factor in student stress is the data analysis method. Alternative stress management for students is taking a short break, doing activities according to hobbies, setting a schedule for meetings with the supervisor, making graduation targets, and thinking positively.